P289 Isolated Mediastinal and/or Hilar Lymphadenopathy: what can EBUS-TBNA add?. (12th November 2015) - Connor, V; Tippet, V; Kennedy, T; Challoner, B
Abstract : Introduction and objectives: In recent years, endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) has been increasingly used to investigate patients with isolated mediastinal and/or hilar lymphadenopathy (IMHL). There is currently a lack of high quality research to confirm the diagnostic yield and accuracy for these patients. The aim of this review was to examine the diagnostic yield of EBUS-TBNA in patients with IMHL, to ensure accurate information is being given to patients considering undergoing the procedure. Methods: A retrospective service review was carried out, including consecutive patients listed for EBUS-TBNA between June 2013–June 2014 in a single UK centre. Results: 135 patients were evaluated who underwent EBUS-TBNA as a first diagnostic test (full results in Table 1). 35 patients with IMHL underwent EBUS-TBNA within the study period; IMHL was defined as the presence of enlarged mediastinal/hilar lymph nodes on computer tomography (CT) without suggestion of intrathoracic/extra-thoracic malignancy. 34 of these had a diagnostic test (97%); pathological cause was found in 9 patients (sarcoid n = 7, malignancy n = 2) with the remaining being diagnosed with reactive lymphadenopathy (n = 25 74%). This group of 35 patients was sub-classified into those with IMHL with a radiologically suggested diagnosis e.g. sarcoid (n = 22) and those with no suggested cause of IMHL (n = 13). EBUS-TBNA was diagnostic in 95% and 100% of patients respectively with the most common diagnosis in both groups remaining that of reactive lymphadenopathy. Conclusions: A significant proportion of patients with IMHL were found to have a diagnosis of reactive lymphadenopathy. With a pathological cause only being found in a minority of cases the appropriateness of EBUS-TBNA to investigate these patients could be questioned. Our results found a significantly higher prevalence of reactive lymphadenopathy than previously published data; Evinson et al . reported this diagnosis 48% of patients and the REMEDY trial reported reactive lymphadenopathy in 5% of patients. The detection of IMHL and its burden on the health service is likely to increase with increasing use of CT. Due to this a large multi-centred prospective study of patients with IMHL would be advisable to further investigate what the most appropriate strategy to manage these patients should be.